2018
DOI: 10.2196/11058
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Needs of Adolescents With Sickle Cell Disease to Inform a Digital Self-Management and Transitional Care Program: Qualitative Study

Abstract: Background Accessible self-management interventions are critical for adolescents with sickle cell disease to better cope with their disease, improve health outcomes and health-related quality of life, and promote successful transition to adult health care services. However, very few comprehensive self-management and transitional care programs have been developed and tested in this population. Internet and mobile phone technologies can improve accessibility and acceptability of interventions to pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 53 publications
0
26
0
Order By: Relevance
“…Another study divided the self-management needs of adolescents with sickle cell anemia into four themes. Some subthemes were concerned with the effect of relationship with peers, the importance of self-management, communication establishment, and social support 42 . In a study conducted by Slater et al (2016) on 16–24-year-old adolescents with permanent musculoskeletal pain, the importance of social support, especially peer groups’ support, was emphasized 43 .…”
Section: Discussionmentioning
confidence: 99%
“…Another study divided the self-management needs of adolescents with sickle cell anemia into four themes. Some subthemes were concerned with the effect of relationship with peers, the importance of self-management, communication establishment, and social support 42 . In a study conducted by Slater et al (2016) on 16–24-year-old adolescents with permanent musculoskeletal pain, the importance of social support, especially peer groups’ support, was emphasized 43 .…”
Section: Discussionmentioning
confidence: 99%
“…This suboptimal knowledge of the medical condition contrasts with what was found in patients with thalassemia and diabetes mellitus, where the majority could name their condition and medication ( 3 ). According to patients, medical knowledge is an important factor in transition readiness ( 11 ). This was confirmed in a systematic review by Stinson et al ( 21 ), which showed that medical knowledge is positively related to transition readiness.…”
Section: Discussionmentioning
confidence: 99%
“…Up to now, SMS and transition readiness have been mainly studied among AYA with non-endocrine diseases such as inflammatory bowel disease, sickle cell disease, kidney diseases or common endocrine disorders such as diabetes mellitus ( 5 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ). For example, Monaghan et al ( 22 ) provide an overview of best practices for health care professionals working with adolescents with diabetes type I who are ready for transition.…”
Section: Introductionmentioning
confidence: 99%
“…When an adequate Hb blood level (men≥13 g/dL, women≥12 g/dL) is not maintained, the disorder complicates the function of the major organs (eg, kidney, brain, and heart) that require oxygen [2]. Anemia, a common Hb disorder, may be caused by blood loss, which is mostly a chronic condition (as occurs with menstruation), decreased red blood cell (RBC) production associated with iron and other nutritional deficiencies, and increased RBC destruction [3,4]. The central role of Hb is to maintain physiologic homeostasis, and the high frequencies of Hb abnormalities make assessment of this parameter a daily clinical activity.…”
Section: Introductionmentioning
confidence: 99%